2010
DOI: 10.1055/s-0030-1248086
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Three Commercially Available Implants Used in Medial Opening Wedge High Tibial Osteotomy

Abstract: This biomechanical study tested three commercially available fi xation devices for medial opening wedge high tibial osteotomy (HTO). A medial opening wedge HTO model was created on replicate tibias.Fixation was achieved with one of three fi xation devices: VS Osteotomy plate (EBI, Parsippany, NJ), Arthrex Osteotomy plate (Arthrex, Naples, Fla), and OsteoTrac plate (DJ Orthopedics Inc, Vista, Calif). For each fi xation system, seven specimens were cyclically loaded in compression and torsion under physiologic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 13 publications
0
18
1
1
Order By: Relevance
“…In our series the Puddu I plate is inadequate for fixation of opening wedge osteotomies, which is in contrast to other authors who have reported good results [6]. Our study led us to abandon the Puddu I plate for medial opening wedge osteotomy.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…In our series the Puddu I plate is inadequate for fixation of opening wedge osteotomies, which is in contrast to other authors who have reported good results [6]. Our study led us to abandon the Puddu I plate for medial opening wedge osteotomy.…”
Section: Discussioncontrasting
confidence: 76%
“…A number of studies have reported on stability of various implants [6,20,23]. These studies have also shown that it is not the axial but the torsional loading which presents problems.…”
Section: Discussionmentioning
confidence: 99%
“…Although biomechanical tests confirmed the adequacy of the fixation and load stability of the Puddu like plates with an insert and without locking head screws [9-11], some authors raised concerns with the first generation Puddu plate in clinical case series [22,26,27]. On the other hand, the biomechanical study by Stoffel et al concluded that the TomoFix plate provides superior stability in both compression and torsion compared to the Puddu Plate and that in the latter case additional fixation might be required [12].…”
Section: Discussionmentioning
confidence: 99%
“…Computer modelling (Specogna et al 2007; Bhatnagar and Jenkyn 2010), cadaveric and gait (Johnson et al 1980; Andriacchi et al 2000; Hurwitz et al 2002) studies have contributed some basic understanding (Andriacchi et al 2000; Chao 2003; Zhim et al 2005; Agneskirchner et al 2006) of the procedure but no method currently exists to plan malalignment correction to minimise excessive knee joint pressure (Dorsey et al 2006; Esenkaya et al 2007; Bhatnagar and Jenkyn 2010). The 2D model implemented in the OASIS software by Chao et al, although capable of estimating contact forces, cannot predict contact stress (Chao and Sim 1995; Chao 2003).…”
Section: Introductionmentioning
confidence: 99%